ABUNDANCE OF POISONOUS BENTHIC DINOFLAGELLATE IN SEAWEED (Sargassum Sp) IN THE COASTAL WATERS OF NIRWANA WEST SUMATRA PROVINCE - Nickson Panjaitan; Irvina Nurrachmi; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe study was held  in  January to February 2019. The purpose of this study was to determine the abundance of toxic benthic dinoflagellates on seaweed Sargassum sp. each station and to see the relationship of abundance of toxic benthic dinoflagellates with the quality of the waters in the seaweed ecosystem of Sargassum sp. in the waters of Nirwana Beach, West Sumatra Province. The method used in this study is a survey method. The results showed the highest genus abundance at the three research stations was the genus Prorocentrum with an average abundance value of 216.05 cells / g and the lowest genus abundance at the three research stations was the Gambierdiscus genus with an average abundance of 78.80 cells / g. Obtained simple linear regression test results show the concentration of nitrate and phosphate concentration is directly proportional to the abundance of dinoflagellates. The relationship between abundance of benthic dinoflagellate abundance with moderate relationship nitrate concentration and the relationship between abundance of benthic dinoflagellate abundance with strong relationship phosphate concentration.Keywords: Dinoflagellata, Benthic, Poisonous, Sargassum sp.